2002
DOI: 10.1074/jbc.m112004200
|View full text |Cite
|
Sign up to set email alerts
|

The Carboxyl Termini of KATP Channels Bind Nucleotides

Abstract: Glutaraldehyde cross-linking demonstrated the multimerization potential of these COOH termini, suggesting that these cytosolic segments may directly interact in intact tetrameric channels. Thus, the COOH termini of K ATP tetrameric channels contain the nucleotide-binding pockets of these metabolically regulated channels with four potential nucleotide-binding sites/channel tetramer. ATP-sensitive or ATP-regulated potassium (K ATP )1 channels couple metabolism to either cell excitability (Kir6.x) (1-6) or potass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 60 publications
4
55
0
Order By: Relevance
“…TNP-ATP Binding-Binding of ATP to these recombinant fusion proteins was performed generally as described previously (19). Briefly, 5 M recombinant protein was dissolved in 50 mM Tris-HCl at pH 7.5, and TNP-ATP binding was detected by the increase in fluorescence (Ex ϭ 403 nm; 546 nm; slit widths 5 nm) upon binding to recombinant protein using a Fluromax-3 spectrofluorometer (Jobin Yvon Inc., Edison, NJ).…”
Section: Dnamentioning
confidence: 99%
See 3 more Smart Citations
“…TNP-ATP Binding-Binding of ATP to these recombinant fusion proteins was performed generally as described previously (19). Briefly, 5 M recombinant protein was dissolved in 50 mM Tris-HCl at pH 7.5, and TNP-ATP binding was detected by the increase in fluorescence (Ex ϭ 403 nm; 546 nm; slit widths 5 nm) upon binding to recombinant protein using a Fluromax-3 spectrofluorometer (Jobin Yvon Inc., Edison, NJ).…”
Section: Dnamentioning
confidence: 99%
“…Production and Purification of Maltose-binding Fusion ProteinsRecombinant proteins were expressed as previously described by us (19). Briefly, 1 liter of Luria-Bertani medium with 0.1 mg/ml ampicillin and 0.2% glucose was inoculated with 10 ml of an overnight culture of BL21 cells expressing the fusion vector and grown to an A 600 of ϳ0.5 at 37°C.…”
Section: Dnamentioning
confidence: 99%
See 2 more Smart Citations
“…Biochemical studies have demonstrated ATP binding to the large C-terminal domain [147,148,151]. Recent studies have used the coordinates of bacterial K + channels [42,82,110] to make homology models the K IR 6.x pore and provide novel information on the adenine-selective, nucleotide-diphosphate-binding pocket, which is composed of residues from both the N-and C-termini (7, 29; reviewed in 5).…”
Section: K Ir 6x Subunits Are Members Of the Inward Rectifier Superfmentioning
confidence: 99%